Evaluation of Soil Total Nitrogen as an Indicator of Soil Bacterial Community Response to Biochar and Plant Growth-Promoting Rhizobacteria Applications - Chenke Ding; Chengqun Lv; Hualin Chen; Jiangmin Zhou; Han Ren (Agronomy, 2024)
Biochar and plant growth-promoting rhizobacteria (PGPR) are widely used as an amendment for soil physicochemical properties and soil bacterial community diversity. In Guangxi, China, we carried out a study to determine how PGPR and biochar influence the soil’s environmental stability in an Eucalypt plantation. We applied biochar and PGPR in a contrasting application manner to an acidic red loam soil. Thus, three treatments were set up as 5 × 1010 CFU·mL−1 PGPR-only (MB0), 20 t·hm−2 biochar-only (B20), and co-application of 20 t·hm−2 biochar and 5 × 1010 CFU·mL−1 PGPR (MB20), as well as no biochar and no PGPR (M0B0). Our results indicated that MB20 significantly decreased the soil total nitrogen (TN) and increased the soil total phosphorus (Soil TP), soil ammonium nitrogen (NH4+), and soil water content (SWC) when compared with the control. The MB20 also significantly increased the Simpson, ACE, and Chao indices of the soil bacterial community’s diversity relative to the control. We also observed a significant effect of the Soil TN on both the bacterial community and the functional diversity in soil. These findings may indicate that assessing the soil N status is expected to be an essential indicator of the soil microenvironment’s response to biochar and PGPR applications.